Laserlithotripsy of common bile duct stones. Issue 6 (June 1988) - Ell, C; Lux, G; Hochberger, J; Müller, D; Demling, L
Abstract : Endoscopic retrograde laser lithotripsy of common bile duct stones is a new technique which can be carried out through the endoscope without anaesthesia using ordinary endoscopic equipment. In the method described here a flashlamp pulsed Neodymium YAG laser (wave length 1064 nm) was used. Light energy was transmitted along a highly flexible quartz fibre with a diameter of 0.2 mm. This new technique was used in nine patients with concrements in the common bile duct, which could not be removed with the established endoscopic techniques. In eight of the nine the concrements (maximum diameter 4.7 x 3.1 cm) could be fragmented and in six the fragments could be extracted from the common bile duct. The total energy required was 80-300 J; complications were not observed.